2020
DOI: 10.1021/acscentsci.0c01262
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Crystal-Phase Engineering of Mesoporous Palladium–Boron Alloy Nanoparticles

Abstract: Rational design and synthesis of noble metal nanomaterials with desired crystal phases (atomic level) and controllable structures/morphologies (mesoscopic level) are paramount for modulating their physiochemical properties. However, it is challenging to simultaneously explore atomic crystal-phase structures and ordered mesoscopic morphologies. Here, we report a simple synergistic templating strategy for the preparation of palladium–boron (Pd–B) nanoparticles with precisely controllable crystal-phases and highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 41 publications
2
47
0
Order By: Relevance
“…Typically, mesoPd/KIT-6 hybrids, in which highly uniform mesoPd with an average nanoparticle size of 176 nm is solidly confined in KIT-6 (Figure S4), were first synthesized with a classic nanocasting method. 21,48,49 Then, the KEST process was conducted by physically mixed mesoPd/KIT-6 and sulfur powder with a weight ratio of 1:1 and directly heat-treated at 150 o C under N 2 atmosphere for 10 h. No solvent or extra reactants are needed in this step. After that, binary h-mesoPdS alloy nanoparticles were collected by washing with H 2 O/ethanol and HF to remove unreacted S and KIT-6 template (see Materials and Methods in Supporting Information (SI) for more details).…”
Section: Resultsmentioning
confidence: 99%
“…Typically, mesoPd/KIT-6 hybrids, in which highly uniform mesoPd with an average nanoparticle size of 176 nm is solidly confined in KIT-6 (Figure S4), were first synthesized with a classic nanocasting method. 21,48,49 Then, the KEST process was conducted by physically mixed mesoPd/KIT-6 and sulfur powder with a weight ratio of 1:1 and directly heat-treated at 150 o C under N 2 atmosphere for 10 h. No solvent or extra reactants are needed in this step. After that, binary h-mesoPdS alloy nanoparticles were collected by washing with H 2 O/ethanol and HF to remove unreacted S and KIT-6 template (see Materials and Methods in Supporting Information (SI) for more details).…”
Section: Resultsmentioning
confidence: 99%
“…The meso ‐Pd nanobundles were synthesized by a traditional nanocasting method with SBA‐15 as the hard template and Na 2 PdCl 4 as the Pd source, [8] while the meso ‐PdP alloy nanobundles were prepared by a concurrent template strategy with meso ‐Pd/SBA‐15 as the template and NaH 2 PO 2 as the P source (Figure S1, see Supporting Information for synthetic details). Here we mostly focused on the characterization of meso ‐PdP alloy nanobundles, since they were inherited from meso ‐Pd nanobundles (completely same mesostructure but different composition) and exhibited a better catalytic performance (see below).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the crystal phase can be controlled by the reaction temperature and time. Recently, Liu and co-workers also found that fcc mesoporous Pd (fcc-mesoPd) confined in a mesoporous silica template and dispersed in a THF solution of DMAB could respectively transform into fcc-mesoPd 5 B after heating at 100 °C for 4.5 h, hcp-mesoPd 2 B-r containing randomly distributed B atoms after heating at 140 °C for 5 h, and hcp-mesoPd 2 B-o containing an atomically ordered B sequence after heating at 160 °C for 5 h. 68 Apparently, the BOC-based synthesis method is effective to synthesize PdB x nanomaterials with a designed morphology and higher B contents. However, the high cost, instability and safety issues of BOCs cannot be ignored in modern catalysis synthesis processes.…”
Section: Boron Atom-doped Pd Nanomaterialsmentioning
confidence: 99%